Generalized Chessboard Structures Whose Effective Conductivities Are Integer Valued. (6th March 2012) - Lukkassen, Dag; Meidell, Annette
Abstract : We consider generalized chessboard structures where the local conductivity takes two valuesa andb . All integer combinations ofa andb which make the components of effective conductivity matrix integer valued are found. Moreover, we discuss the problem of estimating the effective conductivity matrix by using the finite-element method.